2020
DOI: 10.1029/2020gl087373
|View full text |Cite
|
Sign up to set email alerts
|

The Stove, Dome, and Umbrella Effects of Atmospheric Aerosol on the Development of the Planetary Boundary Layer in Hazy Regions

Abstract: Atmospheric aerosol plays critical roles in suppressing planetary boundary layer (PBL) and deteriorating air quality. However, comprehensive understanding on how aerosol optical properties (absorption and scattering) affect PBL remains lacking. Utilizing a large‐eddy simulation model incorporated with in situ observations, we demonstrate distinct impacts of absorption aerosol on PBL development when it is present below (stove effect and promotion) or above morning residual layer (dome effect and strong inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…With the rapid economic growth in China, air pollution has become an issue with large influences on climate, human health and visibility degradation during the last decades (Wang et al, 2015). Wang et al (2020), Ding et al (2016) and Petäjä et al (2016) and other work (Ma et al, 2020) found that atmospheric air pollution can be enhanced by boundary layer-aerosol interactions, characterised by higher aerosol concentrations and shallower boundary layer heights. Therefore, a better knowledge of the long-time variation of the PBL height in China is essential when evaluating variations in aerosol concentrations and effects of regional climate change.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…With the rapid economic growth in China, air pollution has become an issue with large influences on climate, human health and visibility degradation during the last decades (Wang et al, 2015). Wang et al (2020), Ding et al (2016) and Petäjä et al (2016) and other work (Ma et al, 2020) found that atmospheric air pollution can be enhanced by boundary layer-aerosol interactions, characterised by higher aerosol concentrations and shallower boundary layer heights. Therefore, a better knowledge of the long-time variation of the PBL height in China is essential when evaluating variations in aerosol concentrations and effects of regional climate change.…”
Section: Introductionmentioning
confidence: 98%
“…The PBL height is most commonly identified as an inversion in the potential temperature and dewpoint, or as a peak value in the low-level wind speed. Air pollutants are concentrated in the PBL, and the daily variation of the PBL is crucial in interpreting the diurnal variation of air pollutants in areas with anthropogenic emissions (Kaser et al, 2015;Petäjä et al, 2016;Sun et al, 2013;Ma et al, 2020;Xian et al, 2021). In general, the height of planetary boundary layer varies spatially and temporally, typically ranging from about a hundred meters to some kilometres.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the details remain unclear. However, we can foresee that an enhanced frequency and intensity of extreme rainfall and flash floods within and downwind of the gigacity and a decreased amount of total cumulative rainfall (Mahmood et al, 2014;Zhang et al, 2019) are likely to occur. These changes are connected to the increased surface roughness and modified energy and water balances associated with the combination of UHI, high concentration of aerosols and higher fraction of constructed regions.…”
Section: Feedback Mechanisms In the Gigacitymentioning
confidence: 99%
“…Specifically, turbulent motion (i.e., dynamic and thermodynamic) determines the variability of meteorological parameters within the PBL, and consequently affects the change of pollutant concentration. In turn, the change of pollutants also affects the variation of PBL structure ( Ding et al, 2016a ; Ma et al, 2020 ), and even turbulence ( Wilcox et al, 2016 ) by radiation feedback. In addition, the PBL height (PBLH) also plays a vital role.…”
Section: Introductionmentioning
confidence: 99%